1998
DOI: 10.1002/he.10101
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Graduate Student Experience: An Overview

Abstract: In studying the doctoral experience, there is no substitute for on-site, interv i e w, or observation-based data collection. Surveys, however, offer an opport u n i t y to collect information on a broad scale to examine patterns of experience and p a rticularly to investigate the prevalence of certain experiences that people normally associate with graduate school largely because of the stories they hear. The doctoral-student surveys of the Acadia Institute' s Project on Pro f e s s i o n a l Values and Ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 5 publications
0
62
1
Order By: Relevance
“…Department climate, including environmental safety, and developing a culture of caring and respect, has been linked to doctoral student satisfaction (Anderson & Swazey, 1998;Brus, 2006;Protivnak & Foss, 2009;Veilleux, January, Vanderveen, Reddy, & Klonoff, 2012). It is possible that master's students' reduced time spent within a department could shield them from broader aspects of the department that can be problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Department climate, including environmental safety, and developing a culture of caring and respect, has been linked to doctoral student satisfaction (Anderson & Swazey, 1998;Brus, 2006;Protivnak & Foss, 2009;Veilleux, January, Vanderveen, Reddy, & Klonoff, 2012). It is possible that master's students' reduced time spent within a department could shield them from broader aspects of the department that can be problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that the student perspective is vital to exploring dynamics underlying student success (Anderson & Swazey, 1998;Nesheimet et al, 2006;Tinto, 1993), and that student satisfaction can predict achievement and retention (Haworth, 1996;Nerad & Miller, 1996). A majority of the existing research in this area explores the experience of doctoral students and fails to address master's students, particularly in counselor education (Golde & Dore, 2001;Protivnak & Foss, 2009).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…8 Only half of the 1,500 graduate students Melissa Anderson and Judith Swazey surveyed said that faculty were explicit in their expectations of graduate student performance and requirements. 9 In discussing the relationships that faculty build with their students, Lovitts reports that faculty feel that the responsibility for establishing and maintaining a relationship with graduate students lies primarily with the graduate students themselves. Faculty will not go out of their way to establish this relationship.…”
Section: Crl-79mentioning
confidence: 99%
“…Many scholars have stressed the importance of graduate education as a method for socializing graduate students into the norms, mentalities, and expectations for their future careers as experts in their field 1,2,[3][4][5][6][7][8] . In academia, the apprenticeship system of graduate school is designed to help students acculturate to the expectations of their advisors, eventually taking on more authentic, useful, and original tasks, including teaching requirements, grant writing, and mentorship of younger students.…”
Section: Background and Literature Reviewmentioning
confidence: 99%